Evaluating droplet distribution of spray-nozzles for dust reduction in livestock buildings using machine vision - Mehdizadeh, Saman Abdanan; Banhazi, Thomas M (International Journal of Agricultural and Biological Engineering, 2015)
Previous studies have demonstrated the negative effects of sub-optimal air quality on profitability, production efficiency, environmental sustainability and animal welfare. Experiments were conducted to assess potential environmental improvement techniques such as installing oil-spraying systems in piggery buildings. The developed spray system worked very well and it was easy to assemble and operate. However, before selecting the most suitable spray heads, their capacity to uniformly distribute the oily mixture and the area covered by the spray heads had to be assessed. Machine vision techniques were used to evaluate the ability of different spray heads to evenly distribute the oil/water mixture. The results indicated that the best coverage was achieved by spray head No.4 and spray head No.1 which covered 79% and 67% of the target area, respectively. Spray distribution uniformity (variance) value was the lowest for spray head No.4 (0.015). Spray head No.3 had the highest variance value (0.064). As the lowest variance means higher uniformity, nozzle No.4 was identified as the most suitable spray head for dust reduction in livestock buildings. Keywords: spray head, livestock buildings, dust reduction, machine vision, spray distribution uniformity, animal welfare DOI: 10.3965/j.ijabe.20150805.1178 Citation: Mehdizadeh S A, Banhazi T M. Evaluating droplet distribution of spray-nozzles for dust reduction in livestock buildings using machine vision. Int J Agric & Biol Eng, 2015; 8(5): 58－64.